PENGARUH HARGA, PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DI CAFÉ KUPI DATU BANJARBARU - Susiladewi Susiladewi (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2020)
This study aims to determine and analyze the effect of Price, Promotion and Quality ofservices  provided  by  Café  Kupi  Datu  on  customer  satisfaction  both  partially  andsimultaneously. This research is quantitative research. The research design uses formal research   procedures   that   contain   clear   definitions   of   research   objectives   and information needs. To answer and achieve the research objectives, regression analysis will be used. Regression analysis is a statistical method that aims to see the direction of the relationship and the magnitude of influence between 2 or more variables in a linear form. Therefore, the research model in this study is Y = α + βX + e. The results showed that, it turns out that the independent variable that has the largest beta is the Price variable (X1) that is equal to 0.659 or by 65.9%. Therefore it can be said that the variable that has the greatest effect on customer satisfaction Café Kupi Datu is the variable X1 (Price) with a standard regression coefficient of 0.659. The results of the first hypothesis (H1)  are  the  decision  to  reject  H0  and  accept  Ha,  which  means  the  F  test  of  the regression equation obtained from this study shows the results that, together with the three variables price, promotion and quality of service affect the consumer satisfactionat Café Kupi Datu .